Shariah Governance, Audit Quality, and PSAK Syariah Compliance in Islamic Banks - Abukosim Abukosim; Muhammad Farhan; Watim Maysaroh; Riska Tharika (Jesya, 2026)
Integrating Sharia principles into accounting practice still faces structural and technical problems, especially when they don't match up with Sharia-based accounting standards (PSAK Syariah). This study seeks to: (1) analyze the impact of Sharia governance on PSAK syariah (2) Investigate the effect of Shariah governance on audit quality; (3) Analyze the effect of audit quality on compliance with Shariah Financial Accounting Standards (PSAK Syariah); and (4) Examine whether audit quality mediates the relationship between Shariah governance and compliance with Shariah Financial Accounting Standards (PSAK Syariah) in the Islamic banking sector. A quantitative descriptive methodology was utilized, employing multiple linear regression and the Sobel test as analytical instruments. The findings reveal that Shariah governance has no significant direct effect on compliance with Shariah Financial Accounting Standards (PSAK Syariah). In addition, Shariah governance does not significantly influence audit quality, and audit quality itself does not have a significant effect on compliance with PSAK Syariah. However, the results indicate that audit quality plays a mediating role in the relationship between Shariah governance and compliance with PSAK Syariah. These findings suggest that while the direct relationships are statistically insignificant, the indirect mechanism through audit quality provides an important explanatory pathway in understanding compliance with Shariah accounting standards.